A compendium of physical exercise-related human genes: an ’omic scale analysis - Pacheco, Christina; Felipe, Stela Mirla da Silva; Soares, Milca Magalhães Dias de Carvalho; Alves, Juliana Osório; Soares, Paula Matias; Leal-Cardoso, José Henrique; Loureiro, Adriano César Carneiro; Ferraz, Alex Soares Marreiros; Carvalho, Denise Pires de; Ceccatto, Vânia Marilande (Biology of Sport, 2018)
Regular exercise is an exogenous factor of gene regulation with numerous health benefits. The study aimed to evaluate human genes linked to physical exercise in an ‘omic scale, addressing biological questions to the generated database. Three literature databases were searched with the terms ‘exercise’, ‘fitness’, ‘physical activity’, ‘genetics’ and ‘gene expression’. For additional references, papers were scrutinized and a text-mining tool was used. Papers linking genes to exercise in humans through microarray, RNA-Seq, RT-PCR and genotyping studies were included. Genes were extracted from the collected literature, together with information on exercise protocol, experimental design, gender, age, number of individuals, analytical method, fold change and statistical data. The ‘omic scale dataset was characterized and evaluated with bioinformatics tools searching for gene expression patterns, functional meaning and gene clusters. As a result, a physical exercise-related human gene compendium was created, with data from 58 scientific papers and 5.147 genes functionally correlated with 17 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. While 50.9% of the gene set was up-regulated, 41.9% was down-regulated. 743 up- and 530 down-regulated clusters were found, some connected by regulatory networks. To summarize, up- and down-regulation was encountered, with a wide genomic distribution of the gene set and up- and down-regulated clusters possibly assembled by functional gene evolution. Physical exercise elicits a widespread response in gene expression.